2014
DOI: 10.1007/s00484-014-0908-3
|View full text |Cite
|
Sign up to set email alerts
|

Growing-finishing performance and carcass yield of pigs reared in a climate-controlled and uncontrolled environment

Abstract: The objective of this study was to evaluate the effect of temperature on the performance and carcass yield of pigs housed in different environments. Twenty castrated male pigs of the Topigs line were assigned to two treatments: T1, controlled environment, and T2, uncontrolled environment containing a shallow pool. A completely randomized design consisting of two treatments and ten repetitions each was used. The data were submitted to analysis of variance, and means were compared by the Tukey test at a level of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 11 publications
(11 reference statements)
1
12
1
4
Order By: Relevance
“…Swedish Landrace, Large White and Duroc are the three most numerous pure breeds of pigs in the Republic of Serbia, since they exhibit the most desired levels of production properties and provide economic gain. Pork is the most commonly consumed meat in the world (Berton et al, 2015). Many pig breeding programs have been based on estimation and improvement of lean traits (Kawecka at al., 2009) for many years, and this intensive work in breeding has led to significant progress in the meat content of pigs (Rekiel et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Swedish Landrace, Large White and Duroc are the three most numerous pure breeds of pigs in the Republic of Serbia, since they exhibit the most desired levels of production properties and provide economic gain. Pork is the most commonly consumed meat in the world (Berton et al, 2015). Many pig breeding programs have been based on estimation and improvement of lean traits (Kawecka at al., 2009) for many years, and this intensive work in breeding has led to significant progress in the meat content of pigs (Rekiel et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study were related to findings of Choi et al (2010), who showed the importance of environmental control through ventilation/misting installations for pigs by comparing automatic with manual ventilation systems. Berton et al (2015) also observed a worsening FC (P<0.05) for animals in the GF phase that were subjected to climatic variations (uncontrolled environment). The results reinforce the importance of a system for controlling the thermal sensation of animals, improving thermal comfort and performance.…”
Section: Discussionmentioning
confidence: 85%
“…When Berton et al (2015) started this study by evaluating performance and carcass yield, they concluded that animals raised in an uncontrolled environment had a lower (P < 0.05) feed intake and poorer (P < 0.05) feed conversion than pigs raised in a controlled environment, but their weight gain was not affected (P > 0.05) by the treatments, suggesting that animals kept at room temperature, reared in sheds equipped with a shallow pool, perform better than those reared in a controlled environment. Animals raised in controlled and uncontrolled environments did not show differences (P > 0.05) regarding hot and cold carcass weights, carcass yield, and cooling loss.…”
Section: Introductionmentioning
confidence: 99%